2019
DOI: 10.1101/628024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterisation of gastrointestinal helminths and their impact in commercial small-scale chicken flocks in the Mekong Delta of Vietnam

Abstract: Commercial small-scale chicken farms using all-in-all-out production but operating with low standards of hygiene/biosecurity are increasingly common in Vietnam. These conditions facilitate transmission of gastrointestinal helminths. However there are no published data on these parasites in these systems. The aims were: (1) to determine the prevalence/burden of gastrointestinal helminths in small-scale commercial flocks in commercial small-scale flocks in the Mekong Delta region; and (2) to investigate the asso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…The prevalence of Heterakis gallinarum in the current study was 54 (37.5%). This was in line with the work of Solomon and Yobsan 32 , who recorded 33.43%, and Nguyen et al 33 who reported 43.3%. It was lower than the reported rates of 83.3% 7 and 51.6% in Ethiopia 17 , and higher than the previous study in Jimma Ethiopia 9.4% 20 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of Heterakis gallinarum in the current study was 54 (37.5%). This was in line with the work of Solomon and Yobsan 32 , who recorded 33.43%, and Nguyen et al 33 who reported 43.3%. It was lower than the reported rates of 83.3% 7 and 51.6% in Ethiopia 17 , and higher than the previous study in Jimma Ethiopia 9.4% 20 .…”
Section: Discussionsupporting
confidence: 91%
“…It was lower than the reported rates of 83.3% 7 and 51.6% in Ethiopia 17 , and higher than the previous study in Jimma Ethiopia 9.4% 20 . Heterakis gallinarum has a major effect on the health of chickens by sharing feed, thus causing stunted growth and low productivity, which may be related to damage to the intestinal mucosa 33 . The parasite sometimes causes major irritation and inflammation to the mucosa, thus interfering with the absorption of food and showing on the caeca marked inflammation and thickening of the mucosa with petechial hemorrhages.…”
Section: Discussionmentioning
confidence: 99%